2022
DOI: 10.1186/s13023-022-02360-3
|View full text |Cite
|
Sign up to set email alerts
|

The symptom experience of hereditary angioedema (HAE) patients beyond HAE attacks: literature review and clinician interviews

Abstract: Background Hereditary angioedema (HAE) is a genetic disorder characterized by re-occurring swelling episodes called “attacks,” usually in the limbs, face, airways, and intestinal tract. New prophylactic therapies have reduced the frequency of these attacks. This study describes results from a literature review and clinician interviews assessing patient HAE symptom experiences and timing, and then evaluates whether existing patient-reported outcome (PRO) tools adequately reflect this experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…One of the potential limitations of current tools for QoL assessment is that the convenience or side effects of treatments are not considered, even though they may have an important impact on patient QoL. There is a need for larger studies that help to differentiate between disease symptoms and treatment-associated adverse events [65,66].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…One of the potential limitations of current tools for QoL assessment is that the convenience or side effects of treatments are not considered, even though they may have an important impact on patient QoL. There is a need for larger studies that help to differentiate between disease symptoms and treatment-associated adverse events [65,66].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Here, we sought to further build on the earlier research of Castaldo et al [ 1 ] and evaluate the real-world benefits of LTP over a longer time period. Jean-Baptiste et al have recently evaluated the symptom experience of HAE patients and concluded that more research is needed on the effect of longer attack-free durations on HRQoL [ 27 ]. Using data drawn from a wide-ranging survey of members of the US HAEA and Hereditary Angioedema International (HAEi), we examined the relationship between duration of time attack free, and HRQoL, exploring the possibility that there is an association between observed improvement in HRQoL and attack-free duration.…”
Section: Introductionmentioning
confidence: 99%